2020
DOI: 10.3389/fonc.2020.547942
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_000864 Upregulates B-cell Translocation Gene 2 Expression and Represses Migration and Invasion in Pancreatic Cancer Cells by Binding to miR-361-3p

Abstract: BackgroundPancreatic cancer is a fatal disease with a very poor prognosis due to its characteristic insidious symptoms, early metastasis, and chemoresistance. Circular RNAs (circRNAs) are involved in the development of pancreatic cancer.AimHence, the aim of this study is to elucidate the mechanism of circRNA_000864 in regulating BTG2 expression in pancreatic cancer by binding to miR-361-3p.MethodsCircRNA_000864, miR-361-3p, and BTG2 expression patterns in the pancreatic cancer tissues were detected by RT-qPCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Previous studies have identified mounting types of circRNAs playing irreplaceable roles in carcinogenesis [23][24][25]. demonstrated that circRNA_000864 upregulated B-cell translocation gene 2 expression and repressed migration and invasion in PC cells by binding to miR-361-3p [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified mounting types of circRNAs playing irreplaceable roles in carcinogenesis [23][24][25]. demonstrated that circRNA_000864 upregulated B-cell translocation gene 2 expression and repressed migration and invasion in PC cells by binding to miR-361-3p [30].…”
Section: Discussionmentioning
confidence: 99%
“…Jian et al found that circ_001680 affected the proliferation and migration of colorectal cancer and mediated its chemoresistance by regulating BMI1 through miR-340 (26). In addition, some other reports also found circRNAs modulated chemoresistance in pancreatic cancer, lung cancer, and osteosarcoma (27)(28)(29). However, only a few studies investigated the role of circRNAs in regulating chemoresistance in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, circNEIL3 promotes tumorigenesis through the regulation of KLF12 by acting as a ceRNA of miR-137 [ 5 ]. Additionally, studies have demonstrated that cyclic circRNA_000864 absorbs miR-361, relieves the inhibitory effects on the target gene BTG2 in the pancreatic cancer, and promoted tumor proliferation and tumorigenesis [ 6 ]. Moreover, circLARP4 inhibited the development and metastasis of gastric cancer cells by targeting the miR-424/LATS1 axis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%